SPECIALIZED INSTITUTIONS OF THE UNITED NATIONS FOR THE PROTECTION OF CHILDREN’S RIGHTS - Zafar Aktamovich Amirov (Modern American Journals, 2026)
In today’s era of globalization, the protection of children’s rights is considered one of the most important tasks facing humanity. A child is the future of society, and ensuring their healthy development, education, and protection of rights is one of the fundamental factors of sustainable development. Therefore, at the international level, a number of mechanisms have been created to safeguard the interests of children and to ensure their life, health, education, and social protection.